The Role of Periphyton in the Everglades - Pamela Brown; Alan L. Wright (EDIS, 2010)
SL310, a 3-page illustrated fact sheet by Pamela Brown and Alan L. Wright, defines periphyton, describes its role in nutrient cycling for the Everglades ecosystem, and explains the ongoing research related to periphyton in Everglades restoration. Includes references. Published by the UF Department of Soil and Water Sciences, November 2009.